Muscle activation during the tennis volley - Chow, J. W.; Carlton, L. G.; Lim, Y. T.; Shim, J. H.; Chae, M. W.; Kuenster, A. F. (Medicine & Science in Sports & Exercise, 1999)
In general, muscle activity increased with increasing ball speed. The extensor carpi radialis was more active than the flexor carpi radialis during both forehand and backhand volleys, suggesting the importance of wrist extension/abduction and grip strength. The increase in EMG levels in the forearm muscles shortly before the ball impact indicated that the subjects did not tighten their grip and wrist until moments before ball impact. Both antero-middle and postero-middle deltoids were active in most stroke phases. However, the roles of the deltoid muscles during a volley cannot be determined without knowing the actions of the other shoulder joint muscles.